Measuring teachers readiness in implementing vle (virtual learning environment) in primary classroom - Nooryusrina, binti Abdul Rahman (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study aims to investigate the extent to which primary school teachers in Simunjan District are prepared in rolling out VLE (Virtual Learning Environment) as part of e-learning to extend the efforts of institutionalize ICT in education. The specific objectives of this study were to: To assess the extent which teachers are prepared to use electronic technology in teaching, determine their skills and training received in using electronic technology in learning and To assess constraints and hindrances to use of E-learning in primary schools. This study adopted a quantitative research design. The target respondents are in the population of primary school teachers in 50 primary schools in the Simunjan District. A total of 150 questionnaires were distributed. Purposive sampling was used to select samples. This gives a sample of 99 respondents. The questionnaire used in this study to collect data. The data is then compiled and coded for analysis. Percentages, frequency distributions and means were used to analyze the data collected with the help of Microsoft Excel and the Statistical Package for Social Sciences. Data were presented using tables, histograms and pie charts. The findings show that most of the primary schools in Simunjan have Internet access but the service is not satisfactory, teachers lack of skills to use technology in learning is an indicator that they are not yet ready to launch E-learning in primary schools. Overall, the findings suggest that primary schools in the district studied Simunjan are not ready for e-learning. It is recommended that funding for ICT equipment in primary schools in the rural areas should be emphasized again and teachers should be trained to E-learning.